Mental ill health in the elderly: medical students’ social representations in the United Kingdom - Medeiros, Bruno; Foster, Juliet (Revista da Escola de Enfermagem da USP, 2014)
Objective This study aims to explore medical students’ social representations of mental ill health in older adults. Method It comprises an exploratory and qualitative investigation based on the theory of social representations. Two focus groups with pre-clinical medics (group 1, N=4; group 2, N=4) and 10 individual interviews with clinical medical students were conducted. Thematic analysis at a latent level explored meanings and differences between groups. Results Three overarching themes reflect participants’ representations of mental health problems in later life – mental ill health in old age, polarisation of care, and challenges to care. Primary health care appears as an important strategy to overcome barriers to mental health care in the community. Nevertheless, disqualifying representations, stigma and organization of services constitute the main challenges to quality mental health care in later life. Conclusion This paper highlights the need to address cultural and organizational barriers to promote quality care.